Hubungan Verbal Bullying dengan Kecerdasan Interpersonal Siswa Kelas Tinggi - Rukayah Rukayah; Asriadi Asriadi; Rifa Tul Husnah (Universtas Negeri Makassar, 2023)
. This research is a quantitative research with the type of correlational research which aims to: (1) find out the description of verbal bullying, (2) find out the description of students' interpersonal intelligence and, (3) find out the significant relationship between verbal bullying and interpersonal intelligence of high grade students at SDN 243 Ujung Salangketo, Mare District, Bone Regency. The research population was all students in grades IV, V and VI of SDN 243 Ujung Salangketo, Mare District, Bone Regency, amounting to 75 students. The sampling technique in this research is non-probability sampling. Data was collected using a questionnaire. The data analysis technique used descriptive statistical analysis and inferential statistical analysis. Based on the results of descriptive statistics, verbal bullying has an average of 73.04 and a percentage of 60.8% in the medium category and students' interpersonal intelligence has an average of 81.1 and a percentage of 67.5% in the good category. Based on the results of inferential statistical analysis, it was obtained that the t count was -8.43 and the t table with a significance of 5%. of 1.66600 so that t count t table . It can be concluded that there is a negative relationship between verbal bullying and interpersonal intelligence of students at SDN 243 Ujung Salangketo, Mare District, Bone Regency.